2016
DOI: 10.3389/fmicb.2016.01317
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Low Frequency Multi-Drug Resistance and Novel Putative Maribavir Resistance in Immunocompromised Pediatric Patients with Cytomegalovirus

Abstract: Human cytomegalovirus (HCMV) is a significant pathogen in immunocompromised individuals, with the potential to cause fatal pneumonitis and colitis, as well as increasing the risk of organ rejection in transplant patients. With the advent of new anti-HCMV drugs there is therefore considerable interest in using virus sequence data to monitor emerging resistance to antiviral drugs in HCMV viraemia and disease, including the identification of putative new mutations. We used target-enrichment to deep sequence HCMV … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 30 publications
3
76
0
1
Order By: Relevance
“…Others were Q54E/L, D123N, V103A, L56P, L60R, P62Q, L32I, and R34S, which are reported for the first time in this study. However, N-terminal polymorphisms found in this study like Q54 and L56 are close to those found in recently published study by Houldcroft et al [18]. Polymorphisms in N-terminal hydrophobic domain may influence viral interactions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Others were Q54E/L, D123N, V103A, L56P, L60R, P62Q, L32I, and R34S, which are reported for the first time in this study. However, N-terminal polymorphisms found in this study like Q54 and L56 are close to those found in recently published study by Houldcroft et al [18]. Polymorphisms in N-terminal hydrophobic domain may influence viral interactions.…”
Section: Discussionsupporting
confidence: 89%
“…This indicates that pUL27 may have functions potentiated under HIV-CMV co-infection. In common, with recently shown frequent pUL27 polymorphisms in immunocompromised patients [18], we found new polymorphisms in HIV-infected patients. As shown in Table 2, almost 67% of HIV-positive individuals had progressed to AIDS and are therefore considered as severely immunocompromised.…”
Section: Discussionsupporting
confidence: 70%
“…Similar approaches have been used to identify resistant variants of HCV 23 , HBV 24 and influenza virus 25 . partial genomes has been used to detect drug resistance in RNA viruses, such as influenza virus 11 , and DNA viruses, such as human cytomegalovirus (HCMV) 12 . Viral genome sequencing is becoming ever more important, especially in clinical research and epidemiology.…”
Section: Why Sequence Viruses In the Clinic?mentioning
confidence: 99%
“…A good example of this is HCMV, for which WGS can simultaneously capture the genes that encode targets of licensed therapies, such as UL27 (unknown function), UL54 (DNA polymerase) and UL97 (serine/ threonine protein kinase), and of newer drugs, such as letermovir, which targets UL56 (terminase complex). This enables comprehensive antiviral-resistance testing in a single test 12 . In addition, WGS can provide information on antigenic epitopes, virus evolution in a patient over time 12 , and evidence of recombination between HCMV strains 32 .…”
Section: Why Sequence Whole Genomes?mentioning
confidence: 99%
“…As a UL97 inhibitor, maribavir is intrinsically antagonistic to the action of GCV, which requires UL97 for activation. Like GCV, however, maribavir is vulnerable to resistance mutations in UL97 , although at different locations, and resistance has been identified in vitro and in vivo . Maribavir was initially studied in the context of CMV prophylaxis and was ultimately inferior to GCV in the prevention of CMV disease after liver transplantation and HSCT, although it has been suggested this was due to suboptimal dosing (100 mg twice/day) .…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%